2017
DOI: 10.3329/jom.v19i1.34840
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection due to Extended-Spectrum Beta-Lactamase Producing Organisms is a Risk Factor for Acute Kidney Injury among Patients with Type 2 Diabetes Mellitus

Abstract: Background: Urinary tract infection (UTI) is common and diabetic patients are at increased risk for UTI. UTI may be complicated by acute kidney injury (AKI).the world. 3-6 Extended-spectrum beta-lactamase (ESBL) producing strains are an ever increasing problem 7-9 and diabetic patients with long duration and poor glycaemic control are at increased risk for UTI due to ESBL-positive organisms. 5,10 UTI may be complicated by acute kidney injury (AKI) and sepsis. 3 This study was designed to evaluate whether UTI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…This study was in accordance with findings by Selim et al (2019)19 from Egypt who detected bacterial growth in 100% of urine samples from patients with +4 glucosuria level. Mono microbial etiology of UTIs was found to be more common in this study, where E.coli was the most prevalent organism (58.4%); similar findings had been reported by Zubair et al (2019) 14 from Pakistan and Rahim et al 20 from Bangladesh. Out of 103 UTIs caused by E.coli and K. pneumoniae , 25 (24.3%) were due to ESBLs producing isolates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study was in accordance with findings by Selim et al (2019)19 from Egypt who detected bacterial growth in 100% of urine samples from patients with +4 glucosuria level. Mono microbial etiology of UTIs was found to be more common in this study, where E.coli was the most prevalent organism (58.4%); similar findings had been reported by Zubair et al (2019) 14 from Pakistan and Rahim et al 20 from Bangladesh. Out of 103 UTIs caused by E.coli and K. pneumoniae , 25 (24.3%) were due to ESBLs producing isolates.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, ESBLs production appeared as a significant risk factor for acute kidney injury, where all patients with history of AKI had ESBL-UTIs (100%). Same finding were reported by Rahim et al (2018) from Bangladesh 20 and Ramadas et al (2014) from New York 28 . The results of antimicrobial susceptibility revealed that E. coli showed high resistance percentages to ampicillin (78.8%), followed by cefaclor (63.6%), norfloxacin (57.6%) and nitrofurantoin (54.6%).…”
Section: Discussionsupporting
confidence: 83%
“…In 2016, for example, Al Yousef et al,26 isolated 296 ESBL samples and found that diabetes was a risk factor associated with ESBL infection. In addition, Rahim et al,27 found that diabetes was significantly linked to ESBL infection. The current study reveals that diabetes is significantly associated with ESBL infection ( p =0.02).…”
Section: Discussionmentioning
confidence: 99%
“…5 Almost half of T2DM develop ESBL-positive UTIs that might result in acute kidney injury. 6 C-reactive protein (CRP) has been used as an early biomarker predicting bacterial infections and is used as a marker to monitor antibiotic treatment of these infections. 7 Recent reports have suggested the use of CRP blood levels to differentiate acute pyelonephritis (upper UTIs) from asymptomatic bacteriuria in pediatric UTIs.…”
Section: Introductionmentioning
confidence: 99%